THE EFFECT OF OXYTOCIN MASSAGE ON THE SATISFACTION LEVEL OF MIDWIFERY CARE SERVICES FOR POSTPARTUM MOTHERS AT PMB BADARIAH, BATUBARA REGENCY IN 2022 - Fitra Wahdina; Isyos Sari Sembiring; Rosmani Sinaga; Febriyanti Albayumi, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Background:The World Health Organization (WHO), American Academy of Family Physicians (AAFP) Pediatrician Association recommend exclusive breastfeeding for 6 months and continued for up to 2 years. Breastfeeding to babies is the best way of giving food. This is because breast milk contains many benefits that babies need, such as nutritional aspects Method :This research method uses quantitative research with analytical research design and uses a cross sectional approach. The sample taken in this research is 30 respondents using total sampling. Analyzed using Chi Square Test Results : The results of statistical tests using the chi square test, the results of the calculation of p value = 0.001 < = 0.05, it can be concluded that there is a relationship between the quality of midwifery services and the level of satisfaction of postpartum mothers inPMB Badariah, Tanjung Tiram District, Batubara Regency in 2022 Conclusion : Based on the analysis that has been done, there is a relationship between the quality of midwifery services and the level of satisfaction of postpartum mothers